The Development of Patients’ Role Model in Improving Patient Safety Inpatient Room - Julintha Theresia br Sebayang; Setiawan Setiawan; Bustami Syam (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2020)
Patients have a significant role in improving their own safety. Their active involvement in planning, providing health services, monitoring, and evaluating treatment can improve health services. This study aims to develop a model of patients’ role in improving patient safety in the inpatient room at Universitas Sumatera Utara Hospital. It is qualitative research with an action research design. Participants in this study were 15 nurses from 5 inpatient rooms. Data were collected using an online Focus Group Discussion (FGD), using observation form, field notes, and quantitative assessments using a questionnaire. Data were analyzed using content analysis and simple statistics. This study produced 4 models of the patients’ role that can be used in inpatient rooms and increase the nurses’ knowledge about the patients’ role in improving patient safety. This study concludes that the model of patients’ role can be used as a reference in increasing the patients’ role and reducing the occurrence of adverse events when the patients are hospitalized so that patient safety can be achieved.